Design and Construction of Position Sensorless Controller of Permanent Magnet Synchronous Motor with Internal Magnet based on Improved Phase-Locked Loop - Saeed Abazari; Sajad Mohamadi; Gholamreza Arab (هوش محاسباتی در مهندسی برق)
In recent years, the use of permanent magnet synchronous motors has become popular. These engines are cheaper, lighter, and more durable. However, to control these motors, accurate information about the position of the rotor is necessary. For this reason, various methods have been used to improve the motor position estimation performance. One of these methods is estimation by injecting harmonic current into the stator winding. In this paper, using high-frequency currents injected into the stator, the rotor position in IPMSM motors is estimated. However, the response obtained has a DC offset due to the inaccuracy of the current measurement sensors, which causes an error in the estimation of the rotor position. The improved ePLL method was used to solve this problem. This method causes the convergence of the estimated position of the rotor to its real position by removing the noises of the current measurement circuit and the DC offset effect. The efficiency of this method has been proven first by simulation in MATLAB software, then in a Psim environment, and then implemented on the drive of a permanent magnet motor using a TMS320F28034 processor.